2015
DOI: 10.1016/j.tiv.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Soluble extracellular Klotho decreases sensitivity to cigarette smoke induced cell death in human lung epithelial cells

Abstract: Chronic obstructive pulmonary disease (COPD) is currently the third leading cause of death in the US and is associated with an abnormal inflammatory response to cigarette smoke (CS). Exposure to CS induces oxidative stress and can result in cellular senescence in the lung. Cellular senescence can then lead to decreased proliferation of epithelial cells, the destruction of alveolar structure and pulmonary emphysema. The anti-aging gene, klotho, encodes a membrane bound protein that has been shown to be a key re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…There is controversy concerning whether αKlotho present in the lung is produced by resident lung cells or derived from the circulation. Several lung cell lines show αKlotho mRNA expression by RT‐PCR but none express αKlotho protein . On the other hand, Kuro‐o and colleagues discovered that αKlotho could not detect αKlotho transcript in the intact lung, a finding independently reproduced by our group .…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…There is controversy concerning whether αKlotho present in the lung is produced by resident lung cells or derived from the circulation. Several lung cell lines show αKlotho mRNA expression by RT‐PCR but none express αKlotho protein . On the other hand, Kuro‐o and colleagues discovered that αKlotho could not detect αKlotho transcript in the intact lung, a finding independently reproduced by our group .…”
Section: Introductionsupporting
confidence: 60%
“…Endogenous αKlotho transcripts have been detected in cultured lung cells transfected with αKlotho cDNA; yet none of the lung cell lines express αKlotho at baseline . Li et al performed IHC using an unspecified polyclonal anti‐αKlotho antibody, and reported co‐localization with alveolar macrophages and decreased staining in lungs of smokers and patients with chronic obstructive pulmonary disease (COPD); however, control specimens showed high background intensity, and specificity of staining was not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that soluble klotho has protective, anti-inflammatory effects on different cell types (25,26). To test if soluble klotho interferes with the effects of FGF23 in the lung, we co-incubated COPD-BEC with FGF23, cigarette smoke and with the ectodomain of recombinant human α-klotho at 0.1 μg/ml for 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…It is composed of six herbs: astragalus, ginseng, rehmannia, cornus, epimedium and atractylodes, and is effective in treating patients with stable COPD. Previous studies have shown that bufei yishen is safe and effectively alleviates symptoms, and improves lung function in patients with stable COPD [15]. Some domestic scholars have found that the six herbs in the formula not only promote lung and kidney invigoration but also prevent inflammation and aging [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%